2013
DOI: 10.1016/j.jpeds.2012.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Residential Atrazine Exposure and Risk for Choanal Atresia and Stenosis in Offspring

Abstract: Objective To assess the relationship between estimated residential maternal exposure to atrazine during pregnancy and risk for choanal atresia or stenosis in offspring. Study Design Data for 280 nonsyndromic cases and randomly selected, population-based controls delivered during 1999 to 2008 were obtained from the Texas Birth Defects Registry. County-level estimates of atrazine levels obtained from the United States Geological Survey were assigned to cases and controls based on maternal county of residence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 23 publications
2
33
0
Order By: Relevance
“…The authors justified their maternal age analysis based on the higher incidence of gastroschisis in infants born to younger women and the possibility that an ATR-associated risk would be more difficult to detect against a higher age-related background. In the another study conducted by the same group and using the same methods (Agopian et al, 2013a), there was a statistically significant positive relationship between choanal atresia and ATR exposure category when the highest level of exposure (>90th percentile) was compared with the first quartile (OR = 1.79; 95% CI, 1.17–2.74) with evidence of a linear trend ( p = 0.002). The third case–control study in this series (Agopian et al, 2013c) focused on male genital abnormalities.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…The authors justified their maternal age analysis based on the higher incidence of gastroschisis in infants born to younger women and the possibility that an ATR-associated risk would be more difficult to detect against a higher age-related background. In the another study conducted by the same group and using the same methods (Agopian et al, 2013a), there was a statistically significant positive relationship between choanal atresia and ATR exposure category when the highest level of exposure (>90th percentile) was compared with the first quartile (OR = 1.79; 95% CI, 1.17–2.74) with evidence of a linear trend ( p = 0.002). The third case–control study in this series (Agopian et al, 2013c) focused on male genital abnormalities.…”
Section: Resultsmentioning
confidence: 83%
“…Not all studies were entirely independent. The three Canadian studies used data from the Ontario Farm Family Health Study (Savitz et al, 1997; Arbuckle et al, 2001; Weselak et al, 2008), two French studies (Limousi et al, 2013; Migeot et al, 2013) were based on the same data from the district of Deux-Sèvres in the Poitou-Charentes region, and three case–control studies of birth defects in Texas (Agopian et al, 2013a, 2013b, 2013c) performed analyses of the state birth defects registry. The publication dates ranged from 1992 through 2013 with the most recent paper (Limousi et al, 2013) still in press at the time of this review.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Association studies in humans suggest that defects in retinoic acid and FGF signals, hyperthyroidism and exposure to the herbicide atrazine could contribute to choanal atresia [21, 25]. However, it is unclear whether such causes of choanal atresia actually affect the developing embryonic mouth directly.…”
Section: Introductionmentioning
confidence: 99%
“…Several additional case studies [Barbero et al, 2004; Greenberg, 1987; Johnsson et al, 1997], as well as a case–control study [Barbero et al, 2008], have described the occurrence of choanal atresia in offspring of mothers who reported prenatal use of anti-thyroid medication methimazole or propranolol. More recently, a case–control study using data from the TXBDR reported a positive association for isolated choanal atresia/severe stenosis among offspring born to mothers with residential exposure to the herbicide atrazine [Agopian et al, 2013]. Little attention has been given to additional environmental exposures that may contribute to choanal atresia.…”
Section: Introductionmentioning
confidence: 99%